Pengaruh Media Gambar Tunggal Terhadap Keterampilan Menulis Paragraf Deskripsi Siswa Kelas V MIN 11 Kota Medan - Nova Purnama Sari Br. Sitepu; Salminawati Salminawati; Riris Nurkholidah Rambe (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this study was 1) to determine the significant influence of using single image media on students' writing skills in the experimental class, 2) to find out the skills of writing description paragraphs without using students' single image media, 3) to find out the significant use of single image media on students' writing skills in class V experimental class Madrasah Ibtidaiyah Negeri 11 Medan City. The research methodology uses a quantitative approach with the type of Quasy Experiment in the form of Nonequivalent Control Group Design. This research was conducted at MIN 11 Medan City, Kec. Medan Selayang. The population and sample of this study were all students of class V MIN 11 Medan City consisting of 2 classes totaling 72 students and the test instrument used was in the form of an essay. This type of data analysis was carried out by analyzing the paired sampel test. The results of this study indicate 1) the learning outcomes of students who do not use media images obtain an average pretest score of 61,13. 2) the learning outcomes of students who use media images obtain an average posttest score of 75.41. 3) this has a significant effect on media images on the skills of writing descriptive paragraphs as evidenced by the results of the paired simple t test with a value that the t-count is 3,494. After looking at the t-table, namely 2,000. This means that t-count > t-table (3,494 > 2,000) means that Ha is accepted and Ho is rejected.